2013
DOI: 10.1158/0008-5472.can-13-1994
|View full text |Cite
|
Sign up to set email alerts
|

Cancerous Inhibitor of Protein Phosphatase 2A, an Emerging Human Oncoprotein and a Potential Cancer Therapy Target

Abstract: Protein phosphatase 2A (PP2A) complexes function as tumor suppressors by inhibiting the activity of several critical oncogenic signaling pathways. Consequently, inhibition of the PP2A phosphatase activity is one of many prerequisites for the transformation of normal human cells into cancerous cells. However, mechanisms for PP2A inactivation in human cancers are poorly understood. The aberrant expression of cancerous inhibitor of protein phosphatase 2A (CIP2A), a recently identified endogenous PP2A inhibitor in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
162
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 136 publications
(168 citation statements)
references
References 30 publications
6
162
0
Order By: Relevance
“…This obviously requires that the identified interaction and its functional relevance are properly verified by subsequent experimentation or, as it is proposed here, filtered by RRP for their functional relevance. In the case of CIP2A, original identification was made from a single AP-MS purification yielding seven peptides with low Mascot score, and this has translated to over 100 publications establishing the protein as one of the most common cancer driver alterations across human cancers (5,36,37).…”
Section: Discussionmentioning
confidence: 99%
“…This obviously requires that the identified interaction and its functional relevance are properly verified by subsequent experimentation or, as it is proposed here, filtered by RRP for their functional relevance. In the case of CIP2A, original identification was made from a single AP-MS purification yielding seven peptides with low Mascot score, and this has translated to over 100 publications establishing the protein as one of the most common cancer driver alterations across human cancers (5,36,37).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite RB proteins, the mechanisms by which E2F1 expression and activity are regulated during senescence regulation have been elusive. Recently, we demonstrated a previously unidentified positive feedback loop between E2F1 and another human oncoprotein CIP2A (43,44) and demonstrated that this feedback mechanism promotes tumorigenesis by suppressing senescence induction in breast cancer cell lines and in a HER2-driven breast cancer mouse model (17). Rescue experiments demonstrated that senescence induction either by p53 activation, or by direct adenoviral overexpression of p21, was fully dependent on the capacity of these stimuli to downregulate CIP2A expression (17).…”
Section: P21 Mediates P53-induced Senescencementioning
confidence: 95%
“…Importantly, despite a spermatogenesis defect, CIP2A is dispensable for normal mouse growth and development and the adult mice do not show any apparent pathology [19,20]. Consistent with the important role of PP2A in regulating various phosphorylationdependent pathways, CIP2A regulates phosphorylation and activity of many critical signaling proteins in cancer, including MYC, E2F1 and mTORC1-dependent growth signaling [15]. …”
mentioning
confidence: 69%
“…An endogenous PP2A inhibitor protein, cancerous inhibitor of PP2A (CIP2A), promotes malignant cell proliferation, and tumor growth in various cancer models [13][14][15][16]. Overexpression of CIP2A associates with poor patient prognosis and tumor aggressiveness in virtually all cancer types studied thus far, including breast cancer, prostate cancer, and oral HNSCC [14][15]17,18]. In HNSCC particularly, CIP2A seems to be essential for tumor growth as only around 50% of injections of CIP2A negative HNSCC cells resulted in xenograft tumor growth [13].…”
mentioning
confidence: 99%